Geothermal Heat Flow and Thermal Structure of the Antarctic Lithosphere - C. Haeger; A. G. Petrunin; M. K. Kaban (Geochemistry, Geophysics, Geosystems, 2022)
Abstract High‐quality maps of Geothermal heat flow (GHF) are crucial when modeling ice dynamics, shape, and mass loss of the Antarctic Ice Sheet, which is one of the largest potential contributors to sea level rise. The determination of GHF remains challenging, as in situ data are sparse and geophysical models exhibit large discrepancies in amplitude and resolution, especially on regional scales. Using a novel approach implementing a joint inversion of gravity and seismic tomography data with various geophysical and mineral physics information, we estimate the 3D thermal lithospheric structure and present a new GHF map. The resulting surface heat flow correlates with the location of subglacial volcanism and can represent a boundary condition for accurate ice dynamics models that can explain observed acceleration in the ongoing ice mass loss. Absolute values are within the range of other seismology‐based methods and are much lower than those obtained using for example, magnetic data. High uncertainties remain in the parametrization of the upper crustal structure and thermal parameters.